Community pharmacist-administered injectable naltrexone for individuals who were formerly incarcerated: a review of Wisconsin legislation and regulations - Jason S. Chladek; Michelle A. Chui (Substance Abuse Treatment, Prevention, and Policy)
Abstract Opioid use disorder (OUD) is highly prevalent among jail and prison populations in the United States, including in Wisconsin. Medications for opioid use disorder (MOUD), including long-acting injectable naltrexone, are crucial in the treatment of OUD. These medications are especially important for individuals transitioning out of jail or prison and back into the community. Unfortunately, few individuals who were formerly incarcerated continue MOUD after reentry due to a variety of barriers. Wisconsin community pharmacists are highly accessible and uniquely positioned to provide care for this population, specifically by administering injectable naltrexone. However, community pharmacist-administered injectable naltrexone for individuals who were formerly incarcerated has not been previously explored. As a first step, this legislative and regulatory review aimed to identify Wisconsin statutes and administrative codes that may impact these services for this population. Two legal databases were searched to identify relevant Wisconsin statute and administrative code subsections. Overall, 24 statute subsections (from 7 chapters) and 31 administrative code subsections (from 12 chapters) were identified that (1) highlighted a need or potential role of community pharmacist-administered injectable naltrexone for individuals who were formerly incarcerated or (2) served as a potential barrier or facilitator to the availability, access, or use of these services. Future work should focus on helping community pharmacists leverage available resources and overcome existing legal barriers to providing or supporting MOUD services. Importantly, work should be done to ensure that individuals who were formerly incarcerated can be linked to these services upon reentry.